Livid - Emmons, Cai (Book collections on Project MUSE., 2022)
"Sybil White Brown returns from Boston to the small West Coast city where she once lived, hoping to heal after a terrible loss. Summoned to jury duty, she is dismayed to be assigned to the jury of a murder trial alongside her ex-husband with whom she had a rancorous divorce. As the trial progresses, she and her ex tiptoe around each other but eventually become disastrously entangled. Meanwhile, Sybil obsesses about the female defendant, whom she believes is innocent. The situation explodes during jury deliberations when Sybil comes face-to-face with her own unexpressed rage"--